Pengaruh Media Interaktif Berbasis Game Edukatif Terhadap Kemampuan Literasi Siswa Kelas Iv Pada Mata Pelajaran Bahasa Indonesia Di Sd S Pab 2 Helvetia - Sakinah Hasbi; Sahkholid Nasution (Lembaga Teewan Journal Solutions, 2026)
This study aims to determine the effect of interactive media based on educational games on the reading literacy skills of fourth-grade Indonesian language students at PAB 2 Helvetia Private Elementary School. This study used a quantitative approach with a pre-experimental approach and a one-group pretest-posttest design. Thirteen students were selected using a saturated sampling technique. The instrument used was a reading literacy test based on indicators of finding information, understanding, evaluating, and reflecting. Data analysis was conducted using descriptive statistics, normality tests, homogeneity tests, and paired sample t-tests. The results showed that the average pretest score of 39.10 increased to 58.97 in the posttest. Normality and homogeneity tests indicated that the data were normally distributed and homogeneous. The paired sample t-test obtained a significance value of 0.001 < 0.05, indicating a significant effect. Thus, interactive media based on educational games effectively improves students' reading literacy skills.